Sorptive Response Profile of Chitosan Coated Silica in the Defluoridation of Aqueous Solution - Y. Vijaya; A. Krishnaiah (E-Journal of Chemistry)
As excess of fluoride (> 1.5 mg/L) in drinking water is harmful to the human health, various treatment technologies for removing fluoride from groundwater and aqueous medium have been investigated in the past. Present investigation aims to develop chitosan coated silica (CCS) and to investigate the removal of fluoride by CCS through adsorption. Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM), Thermo gravimetric analysis (TGA), X-ray diffraction (XRD) were used for the characterization of the sorbent. The surface morphology of the CCS was observed using SEM. Series of batch adsorption experiments were carried out to assess parameters that influence the adsorption process. The factors investigated include the influence of pH, contact time, adsorbent dose and initial fluoride concentration. The studies revealed there is an enhanced fluoride sorption on CCS. The sorption data obtained at optimized conditions were subjected to Langmuir and Freundlich isotherms. The monolayer sorption capacity, Q° (44.4 mg/g) and binding energy b (0.010 L/mg) have been estimated using Langmuir isotherm. The kinetic studies indicate that the sorption of fluoride on CCS follows Pseudo second-order kinetics.